2017
DOI: 10.1186/s13018-017-0520-4
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of intravenous and topical versus intravenous tranexamic acid in primary total knee and hip arthroplasty: a meta-analysis of randomised controlled trials

Abstract: BackgroundThis meta-analysis aimed to evaluate the efficiency and safety of combined intravenous and topical methods of application versus single intravenous of tranexamic acid in primary total knee and hip arthroplasty.MethodsA systematic search was carried out in MEDLINE (from 1966 to 25 September 2016), PubMed (from 1966 to 25 September 2016), Embase (from 1980 to 25 September 2016), ScienceDirect (from 1985 to 25 September 2016) and the Cochrane Library. Only high-quality randomised controlled trials (RCT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 24 publications
0
36
0
Order By: Relevance
“…The rate of infection is increasing, meaning infections are becoming difficult to treat due to increasing resistance of bacteria to antibiotics. With the passage of time, new antibiotic resistance mechanisms are emerging [6]. In addition, it has been seen in prosthetic joint infection therapy that infections due to Gram-negative bacteria are more unfavorable than those caused by the choice of a therapeutic metal ion in the chitosan complex must be optimized to achieve the desired biocompatibility of the final coating.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of infection is increasing, meaning infections are becoming difficult to treat due to increasing resistance of bacteria to antibiotics. With the passage of time, new antibiotic resistance mechanisms are emerging [6]. In addition, it has been seen in prosthetic joint infection therapy that infections due to Gram-negative bacteria are more unfavorable than those caused by the choice of a therapeutic metal ion in the chitosan complex must be optimized to achieve the desired biocompatibility of the final coating.…”
Section: Introductionmentioning
confidence: 99%
“…Several meta-analyses [ 19 – 21 ] were performed to evaluate the combination of IV and topical TXA in primary TKA. However, it may have some limitations and the conclusion might have the bias: First, as they included both TKA and THA in the analysis [ 19 , 20 ], they did not account for the difference in the type of surgery. It cannot draw meaningful conclusions, and we believed that stricter criteria need to be applied to determine the benefits of combining TXA in a meta-analysis.…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing political and community concern because multiple approaches have failed or struggled to control the spread of HCAIs, resulting in high morbidity and mortality due to AMR infections developed during hospital stays. [150][151][152][153][154][155] Strategies aimed at minimizing and controlling HCAIs comprise active surveillance cultures (ASCs), contact isolation of patients colonized with epidemiologically significant pathogens, and pre-emptive isolation of high-risk patients. 156 It has been suggested that ASCs of all or certain highrisk patients and placing them under contact precautions will help to curb or eliminate the multidrug-resistant organisms (MDROs) that can trigger HCAIs.…”
Section: Screening and Cohorting Patientsmentioning
confidence: 99%